Synthesis and performance optimisation of spray coated Cu2ZnSnS4 absorbing layers from single-source xanthate precursors - Bishop, M.T.; Zhang, L.; Dolganov, A.; Chen, G.Z.; Peng, C.; Hu, D. (Eslevier, 2019)
Cu2ZnSnS4 (CZTS) is a promising non-toxic and cheap absorber layer for the use in photovoltaic cells. In this work copper, zinc and tin xanthates were synthesised and deposited using a single-source spray coating technique to produce CZTS thin films, to investigate how the ratio of these precursors can alter the performance of the device. It was determined that using a tin rich xanthate precursor mix resulted in the thin film with the chemical composition closest to CZTS, with few contaminating phases (i.e. Cu2-xS, Cu2SnS3 and ZnS). To explain this observation, isothermal thermal gravimetric analysis was used to determine rate constants for the decomposition of these xanthate precursors. The rate constants of copper xanthate and zinc xanthate align very well (1.26 and 1.24 s−1 respectively). However, the rate constant for tin xanthate differs significantly (1.09 s−1). Therefore, to form the appropriate ratio in the final product, a tin rich precursor mixture is required. This tin rich xanthate sample was shown to have a band gap of 1.73 eV and a power conversion efficiency of 0.15%.